Samsung's journey to excellence in quality. Issue 2 (15th June 2015) - Shin, Wan Seon; Kim, Chongman
Abstract : Purpose: – The purpose of this paper is to investigate Samsung's strategic efforts in achieving excellence in quality. Design/methodology/approach: – This study divides Samsung's activities into five distinctive areas: quality leadership, motivating employees, methodologies, preemptive priorities and key activities in the field management. Case studies will be explored based on the chronological analysis of the above five subjects, and a comprehensive roadmap toward excellence will also be suggested. Findings: – This study has found that Samsung has used diverse concepts to excel in improving quality and profitability simultaneously. The company's approaches are divided into five categories and positioned according to their possible contributions to excellence. One of the key findings of this paper is the concept of "the line of redundancy" which adopts parallel systems. For example, its parallel systems such as dual sourcing and 120 per cent human resource management have contributed to Samsung's quality. Practical implications: – The result of this study will help managers implement innovative initiatives for achieving excellence through quality management. Originality/value: – Samsung has improved the quality dramatically and many companies want to learn Samsung's way. This paper investigated how Samsung developed the quality system in the past decades and suggests some findings.